Infrared spectroscopic growth studies of an organic semiconductor - Glaser, Tobias; Binder, Martin; Lennartz, Christian; Schildknecht, Christian; Pucci, Annemarie (Physica status solidi. A, Applications and materials science, 2011)
We show an example for sensitive in situ monitoring of organic film growth by means of infrared spectroscopy. The phosphorescent emitter material used in this study was developed for the application in organic light emitting diodes. During thermal evaporation under ultra-high vacuum conditions its vibrational spectrum is monitored and compared to spectra of pristine powder and calculated ones. This comparison proves that the molecules were not destroyed during evaporation and that their mutual interaction in the condensed layer gives rise to only marginal spectral modifications, which indicates the formation of a van der Waals-like solid where the molecular electronic properties are preserved. The development of infrared spectral features with film thickness made obvious that no phase changes occurred during deposition from beginning on up to several ten nanometers thickness. Spectroscopy under different polarization conditions reveals that isotropic layers have formed, which is supported by the special molecular properties of the material under investigation.
Gesehen am 24.06.2022